Jalkut Schimoni zum Zwölfprophetenbuch: Übersetzung und Kommentar - Marx, Farina (Jalkut Schimoni, 2020)
The Yalkut Shimoni is collection of rabbinical commentaries on the Hebrew bible. Research has not yet explained all of the criteria for selecting these commentaries or clarified whether the work was conceived as a comprehensive reference work for exegetic issues, to be combined with the biblical commentary in the Talmud and Midrash, or to reform rabbinical interpretative tradition. This translation is a first step toward resolving these issues